Financial ethics a positivist analysis - Aragon, George A. (New York ; Oxford : Oxford University Press, 2011)
This text provides a framework for the study of financial ethics built on a broad review of mainstream scholarly research published in refereed finance and economics journals. The work is aimed directly at financial academics and students who are likely to be familiar with mainstream financial economics research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Finance -- Moral and ethical aspects